The role of treasury diagnosis on the assessment of the company's financial performance: Practical case study - Mennaa, rima (Finance and Business Economies Review, 2023)
Cash management has become a necessary and essential management tool for managing the company. Hence effective cash management will guarantee the liquidity, solvency and profitability of the company, thus ensuring its financial performance. This article reports a theoretical conceptual framework that illustrates the relationship between cash management and business performance, and how to perform an accurate cash diagnosis to monitor and evaluate the financial performance of the business, at through reports and financial statements (an example on the press company "LE QUOTIDIEN SA"). We arrived at several results, among them: The diagnosis of the cash flow is essential to evaluate the financial performance of a company. Thanks to the study of significant relationships between quantities extracted from financial statements, the ratio method provides a simple approach for assessing the performance of a company. This assessment is generally made on the basis of a comparison between the ratios calculated on the company and reference ratios reflecting significant standards, internal or external. Among the factors which determine the level of performance, mention should be made of the structure of the company's financing. Although the role of this structure is complex, the analysis of the leverage effect provides a first approach, already rich in implications for the assessment of financial performance